DETERMINANTS OF BOND RATING [CASE STUDY ON CONSUMER FINANCE COMPANIES OF INDONESIA STOCK EXCHANGE IN 2018 PERIOD - Hafidania, Rahmi; Hakiman, Hakiman (Dinasti Publisher, 2020)
This study aims to analyze the determinants of bond rating for case studies on consumer finance companies listed on the IDX. The factors studied are firm size, liquidity, profitability, leverage, and growth. The sample collection technique uses a purposive sampling method. The data used descriptive statistical analysis with total 22 sample companies. Data analysis uses multiple linear regression analysis. The results showed that firmsize and liquidity had a significant positive effect, while the leverage had a negative effect on bond rating. Profitability and growth had no effect on bond rating. The implication of this study is that investors can make information related to bond rating as one of the references before making an investment and to minimize the risk of default. In order for bonds to remain competitive and attractive to investors, companies need to improve company performance and bond rating. In addition, companies also need to increase assets and strengthen capital for business turnover. These ways have been proven affecting the company's obligation rating. For further study, it is expected to be able to test other variables that are determinants of bond rating because the coefficient of determination of this study is 63.70%, which means the remaining 36.30% bond rating are influenced by factors outside this study.